Whiting Griswold correspondence - Griswold, Whiting, 1814-1874.
Letters addressed to Griswold relating to political parties such as the American Party (also known as the Know-Nothing Party), the Democratic Party, Free Soil Party, and the Whig Party; local, Massachusetts state, and national politics; the 1853 Massachusetts Constitutional Convention; patronage; the Kansas-Nebraska Act; the Civil War; the Hoosac Tunnel, Mass.; and Griswold's legal practice. Correspondents include Nathaniel Prentiss Banks, George S. Boutwell, Benjamin F. Butler, Caleb Cushing, Benjamin Franklin Hallett, George Frisbie Hoar, George B. Loring, Wendell Phillips, Charles Sumner, James Lyman Whitney, and Henry Wilson.
Lawyer and politician.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Banks, Nathaniel Prentiss, -- 1816-1894 -- Correspondence; Boutwell, George S. -- 1818-1905 -- Correspondence; Butler, Benjamin F. -- 1818-1893 -- Correspondence; Cushing, Caleb, -- 1800-1879 -- Correspondence; Hallett, Benjamin Franklin, -- 1797-1862 -- Correspondence; Hoar, George Frisbie, -- 1826-1904 -- Correspondence; Loring, George B. -- 1817-1891 -- Correspondence; Phillips, Wendell, -- 1811-1884 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Whitney, James Lyman, -- 1835-1910 -- Correspondence; Wilson, Henry, -- 1812-1875 -- Correspondence; Massachusetts. -- Constitutional Convention -- (1853); American Party; Democratic Party (U.S.); Free Soil Party (U.S.); Whig Party (U.S.); United States; Constitutional conventions -- Massachusetts; Patronage, Political; Political parties -- United States; Practice of law -- Massachusetts; Tunnels -- Massachusetts; Hoosac Tunnel (Mass.); Massachusetts -- Politics and government; United States -- Politics and government -- 19th century; United States -- History -- Civil War, 1861-1865.; Lawyers; Politicians